Ajustes nutricionais para suínos em crescimento e terminação através de uma ferramenta de nutrição de precisão - Lovato, Gustavo Dias (2013)
The work was realized with objective to use InraPorc® model as nutritional adjustment tool for growing and finishing pigs, in Brazilian commercial production context. The pre-experimental period was realized in a production commercial unity of swine with capacity to 432 pigs. This period was realized data collection to nutritional program definition, calibration of animal profile and nutritional adjustments. Animal profile was collected through weighing of 20% of pigs and monitoring feed intake each pen. The data collected was inserted in the InraPorc® to make the simulations and to propose adjustments to conventional nutritional program. Already in the experimental period was realized a comparison between conventional nutritional program (CNP) and adjusted nutritional program to estimate nutritional requirements through InraPorc® for the animal profile in study (ANP). Were utilized 432 pigs with average body weight of 21.9kg in a completely randomized design. The pig performance do not affected (P>0.05) by nutritional programs. On experimental period, the daily intakes of digestible lysine, total phosphorus and digestible phosphorus in the CNP was higher (P<0.01) than ANP. The pigs of CNP had backfat thickness 8% higher (P<0.05) than pigs of ANP. On Brazilian commercial production context, the InraPorc® model can be utilized with advantage in the adjustment of nutritional programs for growing and finishing pigs.